Nonverbal Immediacy Mediates the Relationship Between Interpersonal Motives and Belongingness - Mayor, Eric (Frontiers in Sociology, 2020)
While belongingness is a predictor of mental and physical health, the lack of social bonds is an issue for many people in occidental countries. This issue calls for global and affordable solutions. In this study, we notably investigated (a) the presumed positive relationships between agentic and communal interactional motives and belongingness, and (b) the mediating role of self-reported nonverbal immediacy – an indicator of availability to interact – in these relationships. Cross-sectional and longitudinal data were collected by means of questionnaires to test these hypotheses (NCrossectional = 344; NLongitudinal = 126) using the General Belongingness Scale, the Nonverbal Immediacy Scale, and the Bem Sex Role Inventory. Results supported the hypotheses: Interpersonal motives and nonverbal immediacy are associated cross-sectionally to belongingness, nonverbal immediacy mediates the interpersonal motives – belongingness relationship and positive changes in nonverbal immediacy is also related to increased belongingness. Practical and research implications are discussed.